The Role of Denosumab as an Adjuvant Treatment in the Bone Tumor of Giant Cells: Case Report - Karla, Aguirre; Gerardo, Durán; Angela, Morales; Acosta, Serrano; Elizabeth, Arellano; John, Dorado (British Journal of Healthcare and Medical Research, 2024)
The bone tumor of giant cells represents 5% of primary bone tumors and is classified as locally aggressive. For treatment it is important to make the differentiation between resectable or unresecable tumor. Currently, the great role of Denosumab has been established as a post -operative adjuvant treatment. Although at the beginning of its approval for this tumor, its administration was preoperative, with subsequent studies it was observed that this only increased recurrence. We present the case of a female patient of the fifth decade of life, who has had an excellent answer: clinical and of imagen based on the RECIST criteria, with post operation neoadyuvant treatment with denosumab, after partial loaf resection in an unresecable tumor to be in the skeleton axial.